1989
DOI: 10.1007/bf00127458
|View full text |Cite
|
Sign up to set email alerts
|

Parent surveys for school teacher evaluation

Abstract: The improvement of public school teacher evaluation is a topic of considerable interest in the research literature and in professional practice. One suggested direction for better evaluation is to develop sources of data about teacher performance in addition to the traditional administrator reports. Principal visits, particularly as a sole data source about teachers, have been criticized as inadequate and even misleading. Parent viewpoints of teacher performance have been discussed by a number of authors as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 11 publications
1
27
0
5
Order By: Relevance
“…Overall, the results indicate that the students' evaluations of the teachers' teaching were reliable. This is consistent with the findings of Peterson, Wahlquist, and Bone (2000), who have shown that secondary school students could give reliable evaluations of their teachers' educational practices. The finding of this study is also in agreement with the result of Irving (2004), who finds that secondary school students' evaluation of teachers was reliable in a study conducted in 13 states in the USA.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the results indicate that the students' evaluations of the teachers' teaching were reliable. This is consistent with the findings of Peterson, Wahlquist, and Bone (2000), who have shown that secondary school students could give reliable evaluations of their teachers' educational practices. The finding of this study is also in agreement with the result of Irving (2004), who finds that secondary school students' evaluation of teachers was reliable in a study conducted in 13 states in the USA.…”
Section: Discussionsupporting
confidence: 92%
“…In reporting on the use of teacher dossiers, a streamlined version of portfolios, Peterson (1988) noted a high reliability rate in making teacher promotion decisions for a career ladder system. Twenty-six career ladder panelists judged 12 teacher dossiers, and the "panelists showed a 90.4 percent agreement level on the 312 promotion judgments.…”
Section: What Evidence Supports the Use Of Portfolios For Teacher Evamentioning
confidence: 99%
“…He concluded that Badministrator reports, the conventional practice, showed low correlations with other measures'' (p. 316) of teacher quality. Peterson (1989a) found statistically significant difference in return rates and ratings of parent surveys according to the age of the pupils: parents of younger students returned surveys at higher rates and were more positive about teacher performance. He found that some teachers had stable patterns of parent ratings over several years, while other teachers varied according to the particular year.…”
Section: Conceptual Basis For Including Parent Views In Teacher Evalumentioning
confidence: 81%
“…The original survey designed for this study did not include Bpopularity'' items (e.g., BChild treated as an individual'') which may lead to ratings more based upon trivial and superficial pleasing teacher performances, sometimes called Bpandering,'' rather than more defensible substantial performances such as fostering student learning in the classroom, enabling home support of learning, and providing important information for parents as legitimate stakeholders (Epstein, 1985;Peterson, 1989aPeterson, , 2000Scriven, 1973Scriven, , 1988. However, the multiple authors of the actual survey used in this study resulted in using some items not tested in previous studies (e.g., BChild treated as an individual'').…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%